The Effectiveness of Using Electronic Stick Figures for Teaching Writing Recount Text at Junor High School (RETAIN, 2014)
The Effectiveness of Using Electronic Stick Figures for Teaching Writing Recount Text at Junor High School Fatmah Mahardini English Department, Languages and Arts Faculty, State University of Surabaya fatmah_mahardini@yahoo.com Prof. Dr. Hj. Lies Amin Lestari, M.A., M.Pd English Department, Languages and Arts Faculty, State University of Surabaya lies.aminlestari@yahoo.com Abstrak Menulis dianggap sebagai keterampilan yang paling sulit diantara keterampilan berbahasa lainnya (membaca, berbicara, dan mendengarkan). Sehingga para guru perlu menemukan berbagai cara kreatif untuk pengajaran writing (menulis) daripada hanya meminta siswa menulis tanpa memikirkan bagaimana memberi kemudahan kepada siswa dalam belajar menulis. Karena alasan tersebut, media dibutuhkan dan seharusnya digunakan untuk membantu siswa dalam menguasai kemampuan menulis. Selain itu, penggunaan multimedia dalam proses belajar mengajar dapat membuat materi pembelajaran lebih mudah diingat dan dimengerti. Teori yang mendasari penggunaan multimedia adalah Dual-coding yang dibuktikan oleh Paivio (1986). Olehkarena itu, electronic stick figures dalam bentuk multimedia dipercaya sangat sesuai untuk pengajaran menulis teks recount. Penelitian ini menggunakan desain penelitian eksperimental dengan sampel penelitian yakni grup eksperimen dan grup kontrol yang bertujuan untuk mengetahui efektivitas penggunaan electronic stick figures untuk pengajaran menulis teks recount pada siswa kelas delapan di SMP Negeri 1 Ngoro. Sehingga penelitian ini dilaksanakan untuk mencari perbedaan nilai writing yang signifikan antara grup yang belajar writing menggunakan electronic stick figures dan group yang hanya menggunakan buku dan papan tulis. Nilai-nilai post-test dari kedua grup dibandingkan dengan menggunakan perhitungan t-test. Hasil dari perhitungan tersebut menunjukkan bahwa experimental group yang belajar menulis menggunakan electronic stick figures menunjukkan peningkatan nilai yang signifikan dibandingkan dengan siswa di control grup dengan nilai t 6.067 dan nilai p .0001(df= 88, perbedaan nilai rata-rata9.95). Hasil tersebut menunjukkan bahwa penggunaan electronic stick figures efektif untuk meningkatkan kemampuan siswa dalam menulis teks recount. Kata Kunci: pengajaran writing, electronic stick figures, recount Abstract Writing English is considered as the most difficult skill among the other language skills (reading, speaking and listening). Therefore, it is important for the English teachers to find some creative ways to teach writing instead of only directing student to write without thinking how to facilitate them. Because of that reason, appropriate media is needed and should be used to help students master writing. Moreover, the use of multimedia in teaching and learning process is able to make the lesson become memorable and understandable (Mayer and Simes, 1994). The theory which underlies the use of multimedia is Dual –coding which was proven by Paivio (1986). Therefore, Electronic stick figures in the form of multimedia are believed considerably suitable for teaching writing recount text. Using experimental research design with experimental and control group as the sample, this study was aimed to find out the effectiveness of using electronic stick figures for teaching writing recount text at eighth graders of SMP Negeri 1 Ngoro. Thus, this study was conducted to find the significant difference in term of students’ writing scores between students who are taught by using electronic stick figures and those who are taught by using only book and whiteboard. Using t-test calculation, the scores of post-test of the two groups were compared. The result showed that by using electronic stick figures students in the experimental group scored significantly higher than students in the control group, with the t value of 6.067 and p value of .0001 (df = 88, mean difference 9.95). It shows that the use of electronic stick figures is effective to improve students’ ability in writing recount text. Keywords: Teaching Writing, electronic stick figures, recount INTRODUCTION Students in Junior High School are aimed to be able to communicate both oral and written in functional literacy level (Depdiknas, 2006). In Functional literacy level, students are directed to be able to use English in their daily life for the purpose of transactional communication, such as read manual, understand the meaning of signs, and create functional texts or simple essay. To gain this aim, Junior High school students are taught four English language skills (listening, speaking, reading and writing) equally. As stated by curriculum maker 2006 ,the scope of English lesson in junior high school includes a) the ability to understand and/or create oral and or written texts which will be presented by the combination of listening, speaking, reading, and writing to reach functional literacy level, b) the ability to understand and create short functional texts, monologues and essays in the form of procedure, descriptive, recount, narrative, and report text, c) supportive competence, such as : linguistic, socio-cultural, strategic, discourse competence. Furthermore, recount text is included in the scope of English lesson for Junior High School. The standard competence of writing recount text appears in eight grade of junior high school. It is taught in both odd and even semester. Based on the 2006 curriculum, recount text is taught to eighth and ninth graders in Junior High School. It seems that recount is required to be taught since this level because it has many functions in daily life such as in letter, conversation, and etc. Students often tell their experience in form of recount, but they do not realize that it is in form of recount. Recount is usually compared to narrative. Both look similar, but actually they are not the same. Both of them tell about past event. Narrative tells readers about problematic event which is usually fiction. In contrast, recount does not come to a serious crisis complication and it is usually based on fact. Furthermore, Anderson and Anderson (2003: 24) conclude that a recount text is a piece of text that retells past event, usually in the order in which they occurred, and has purpose to provide the audience with the description of what happened and when it happened. Moreover, Derewianka (1990) states the focus of recount is on a sequence of events, all of which related to a particular occasion. Focusing on the sequence of event may differentiate recount to narrative which focus on a serious crisis of complication and its resolution, besides fiction form. Thus, recount must be taught as clear as possible in order to make students able to write recount in an appropriate text form. However, most of students consider writing as the most difficult skill among the other. As stated by Richard (1997: 100), mastering writing is difficult and needs lengthy process because of anxiety and frustration for many learners. They may reluctant to write because they are de-motivated during the lesson. Furthermore, students are usually confused when they are going to start writing (Emilia, 2008). It seems that they have nothing in their mind about what they are going to write. Sometimes they also have difficulties to express their ideas and have limited vocabularies in producing the text both oral and written. For those reasons, teacher must be aware about the difficulties which are faced by students when they learn writing. As a result, the teacher should take into consideration on some principles to teach writing. Nunan (2003:92) suggests some principles in teaching writing that purposes to make efficient of teaching. These principles can be adapted to the many different learning situations. Firstly, the teachers should understand the students’ reason for writing before going to writing class. In other words, teachers try to expose the students to the usefulness of the activity. It is because students mostly feel dissatisfaction when their goal to write is not suitable with the teachers’. Hence, the teachers should be careful in making writing instruction that match students’ goal. Secondly, the teachers should encourage them to make beneficial effort as much as possible and provide many opportunities for students to write. Because writing is a skill, students need more practices to write. Thirdly, make feedback helpful and meaningful. Students need feedback on their writing although it doesn’t always have intended effect. In other words, teacher may be a motivator, resource, and feedback provider (Harmer, 2001: 216). Teachers sometimes find the difficulties too in the way they explain students about how to write recount text appropriately. This situation usually appears when students seem de-motivated during the lesson. Students are not able to enjoy the lesson because learning writing is such a boring moment. Consequently, students cannot grab the point from teacher’s explanation. From the previous explanation, both teacher and students face difficulty in teaching and learning process. Therefore, teachers should try to find an appropriate and interesting way stimulate students’ excitement in writing activity. There are many possible ways and facilities to support teaching and learning English i.e., exploiting available facilities around us, teachers are aimed to be able to use them efficiently to deliver any information to their students. Furthermore, Brown (2001) and Ur in harmer (2002) called adolescents as teens or young adults who are ranged between 12 and 18 year- old learners which still consider varieties of sensory input as essential factor to assist them in understanding things. In other words, adolescents need alternative material and media in learning language. Adolescents are over all the best learners (Ur, 2000). It is the best time for them to develop their intellectual maturation so teacher should apply creative teaching and facilitate them with suitable media. They also need guidance from the teacher to get maximum result. Thus, material and media used by students should be selected carefully. Nowadays, there are many kinds of media or tools that we can use to deliver information to the students. Anything that can be used to help teacher express or convey what is going to explain to students is called teaching media, also called teaching aids Martin and Brings, 1986). Since technology is rapidly developed, computer becomes a novelty and common thing in educational field. It shifts people’s view to the way of teaching (Sudjana and Rivai, 2007:110). Many educators believe that technology as supporting media in language teaching can overcome the weaknesses of traditional media which is used long before the trend of technology. In the past, teachers taught their students by using traditional media such as blackboard, books, papers, cards, etc. While, nowadays there are many kinds of teaching media which provide certain features for each purpose which are made by computer systems. Furthermore, Abdelraheem & Al-Rabane (2005) explain that technology has a big potential to be encouraged as a tool that can overcome the traditional setting of the classroom which is isolated (Braune,1997) supply access to rich resources (Becker &Ravitz, 1999) and increase overall productivity (Saye, 1998). Thus, it is clear that technology use can create such an easier way of language learning. According to Lesman et al (2009), nowadays, the use of new media is increasing rapidly such as video, educational television, on-line web, blog, and computer games. Since computer becomes a common thing, many kinds of media are created in various forms such as visual aids, audio aids, audiovisual aids, and multimedia. Multimedia is one type of media that can be used to express/ convey what is going to tell to student, whether software or manual. It provides several kinds of teaching aids. It does not only provide one kind of media, such as audio only, but it can provide more than one kind of media. As technology development has touch every part of our life and as education is part of our world, it is interesting to make use of innovative tools and bring it inside classroom. There are a lot of advantages in using computer and multimedia for teaching language in the classroom. We often find a teacher teach a large number of students in the class. Teacher can apply the media which can be shown in a large screen by using computer and LCD projector so it can grab students’ attention. It can also minimize the time consuming compared to the drawing on the blackboard which need time to draw on the blackboard. By the unique features of multimedia, students are interested to learn. Moreover, Marentette and Uhrick (2008) in their article say that the use of multimedia promotes meaningful learning that can be transferred or generalized to other situations. They add that learning is constructive, and information learned is remembered at a deeper level. Besides, multimedia can also improve the academic engagement of students so students can take a part and experience themselves by operating it. MCALL or multimedia courseware is a set of software programmed to help users learn something. The theory which underlies and supports the use of Multimedia courseware in language learning is Dual Coding Theory. Based on dual coding theory stated by Paivio (1986:53), humans have separated information channels, verbal and visual. Their systems are interconnected but each can work independently. He describes that when dual coded, information will be easier to retain and retrieve because the availability of two mental representation instead of one. Therefore students who are taught using multimedia can grab the information easily. Paivio (1991:5) adds that